A Striking Exception to the Chelate Model for Acyclic Diastereocontrol: Efficient Access to a Versatile Propargyl Alcohol for Chemical Synthesis - Ronald J. Clark; Gregory B. Dudley; Sami F. Tlais (Molecules, 2009)
The four-step, asymmetric synthesis of a chiral propargyl alcohol 1 from (R)-pantolactone is described. A key feature of the synthesis is a diastereoselective acetylide addition to a chiral α-alkoxy-aldehyde 7, in which unusual Felkin selectivity is observed, despite the potential for chelation control. Crystalline propargyl alcohol 1 is valuable for complex molecule synthesis, and is easy to prepare in multi-gram quantities and high diastereomeric purity.